Environmental DNA metabarcoding of foraminifera for biological monitoring of bottom water and sediments on the Takuyo-Daigo Seamount in the northwestern Pacific - Maeda, Ayumi; Nishijima, Miyuki; Iguchi, Akira; Ota, Yuki; Suzumura, Masahiro; Suzuki, Atsushi (Frontiers in Marine Science, 2024)
Foraminifera are adapted to a wide range of environments, and environmental DNA (eDNA) metabarcoding of foraminifera should facilitate development of new environmental indicators. In this study, we used eDNA metabarcoding to evaluate the discrepancy between planktic and benthic foraminifera molecular communities identified in bottom water and short sediment cores. The molecular community was compared to foraminiferal shells in sediment traps set on the seafloor. Samples were collected in June and August around the Takuyo-Daigo Seamount in the western subtropical Pacific Ocean. Approximately 40% of amplicon sequence variants (ASVs) pertained to unknown foraminiferal lineages in sediment samples, compared with only 22% in bottom water. Bottom water contained benthic foraminifera and taxonomically unassigned lineages, which were attributed to resuspended particles. In bottom water, 100 ASVs were assigned to planktic foraminifera. ASVs assigned to Candeina nitida were most abundant and accounted for 36–86% of planktic foraminiferal ASVs. In sedimentary DNA, Globigerinita glutinata was the most abundant among 33 ASVs of planktic foraminifera. However, transparent shells in sediment traps contained more spinose species, such as Globigerinoides ruber, whereas C. nitida was not found and few G. glutinata were detected. This discrepancy between the three samples may be due to the species-specific preservation, to PCR biases, and/or to low abundance of planktic foraminifers. In sedimentary DNA, 893 ASVs were assigned to high-level foraminiferal taxa. Among benthic foraminiferal lineages, monothalamids were most abundant, as reported in other deep-sea regions. Molecular communities formed one cluster above the boundary at which ASVs sharply decrease across the three cores. Our results suggest that depth within the sediment core can affect foraminiferal ASVs, but the distance between sites up to 200 m did not strongly affect ASVs of sedimentary DNA at least above the boundary at which ASVs sharply decrease. Sequences of foraminiferal DNA in sediment decreased linearly in core PC02-A1, but exponentially in core PC03-B3. The decline of foraminiferal ASVs may reflect both the decreases in numbers of living foraminifera and degradation of DNA in sediment, related to the particle mixing depth.